Pengaruh Influencer Marketing, Motivasi Diri, Dan Pengetahuan Investasi Terhadap Pengambilan Keputusan Investasi Saham (Studi Kasus Mahasiswa Universitas Mataram) - Maulida, Baiq Irma Uriwatin; Effendy, Lukman (Universitas Mataram, 2024)
This research was conducted to analyze deeply how influencer collaboration influences stock investment decision-making among students, as seen through increased self-motivation and investment knowledge. The method used in this study is quantitative with descriptive statistics and partial least square structural equation modeling (PLS-SEM) analysis using SmartPLS 4. Data collection was carried out using a questionnaire technique. The sample of this study consisted of 150 students from the Faculty of Economics and Business, University of Mataram. The research findings indicate that influencer marketing, self-motivation, and investment knowledge have a significant positive influence on stock investment decision-making. These findings provide insights for university stakeholders to enhance motivation and investment knowledge among students and optimize the use of influencer marketing